Pelatihan Pembuatan Google Form Sebagai Media Evaluasi Pembelajaran bagi Guru SD Gugus V Lingsar - Amrullah Amrullah; Nani Kurniati; Muhammad Turmuzi; Ni Made Intan Kertiyani; Wahidaturrahmi Wahidaturrahmi (Rengganis Jurnal Pengabdian Masyarakat, 2023)
Observations and interviews conducted with elementary school teachers in cluster V Lingsar obtained the result that teachers were still evaluating manually using paper. Teachers need practical and effective evaluation media to save time on correcting answers. Reflecting on this need, community service activities are carried out to provide training on using the google form as a practical and effective evaluation medium. The activity participants consisted of 20 elementary school teachers in cluster V Lingsar. Activities consist of delivery of material and practice. All participants gave a positive response to the activities carried out because these activities were in accordance with the needs of the participants.